Pemberdayaan Karang Taruna Bina Bangsa Anrang Bulukumba dalam Pemanfaatan Limbah Biji Durian sebagai Bahan Dasar Adonan Biskuit - Mudyawati Kamaruddin; Ratnasari Dewi; Nurhidayat Triananinsi; Abdul Haris Mubarak; Diawan Cahyawan; Mukrimah Mukrimah; Eka Kurnia; Pia Pia; Andi Harmawati (Jurnal Surya Masyarakat, 2023)
Every durian season, there is an abundance of durian seed waste in Anrang village, Bulukumba district, South Sulawesi. This gives the impression of a village environment piled high with garbage in the form of durian seeds and skins. The goal of this community service project is to assist the Anrang village community, through the Anrang Youth Organization, in converting waste durian seeds into flour, which will be used to make biscuits. Using the project-based learning method, this activity provides counseling, training, and direct assistance to members of Karang Taruna Anrang. The activity produced very satisfactory results, with a product in the form of durian seed flour that provided a suitable taste and structure as a biscuit ingredient. Durian seed flour has a pleasant taste, structure, and aroma, making it an excellent potential ingredient for biscuits.